Sustainability Reporting and Artificial Intelligence: A Systematic Literature Review - Mareta Putri; Inten Mutia; Shelly Febriana Kartasari (Jurnal Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study aims to evaluate the role of Artificial Intelligence (AI) in sustainability reporting. The main focus is on how AI can improve quality, efficiency, and transparency, as well as the challenges that arise in the application of AI in sustainability reporting. Methodology/approach: The method used was a Systematic Literature Review (SLR) with three stages: planning, implementation, and reporting over the past five years (2020-2025) from 1,087 initial articles. After the PRISMA process, 30 relevant articles were selected and analyzed. Results/Findings: The study found that the benefits of AI include improved efficiency and accuracy, management of big data, enhancement of transparency and accountability, and aiding in sustainable decision-making. The main challenges of this research are algorithm bias, personal data protection, cost and technology constraints, and the lack of global standards in AI-based reporting. Conclusions: AI has the potential to improve quality and transparency through automation, predictive analysis, and efficient data management. However, its implementation requires regulations, guidelines, and ESG standardization. Limitations: Most studies originate from developed countries, while developing countries contribute relatively little. Contributions: This research highlights the importance of regulation and standardization in the implementation of AI in sustainable financial reporting. It describes the current state of affairs and provides a strong foundation for further research and policy formulation at the global level.